Sistem Pendukung Keputusan Penerimaan Beasiswa Tahfidz dan Kip-K dengan Metode SMART Pada STMIK Antar Bangsa - Nur Fadillah; Chandra Kirana Az-Zahra; Hayatun Nufus; Subhiyanto (Jurnal Sistem Informasi, 2025)
The selection process for KIP-Kuliah and Tahfidz scholarships at STMIK Antar Bangsa is still conducted manually through several stages, such as document collection, computer-based tests (CAT), interviews, and file evaluation through plenary meetings. This process often causes delays and carries the risk of subjective assessments, especially when the number of applicants increases significantly. This research aims to design a decision support system implementing the Simple Multi Attribute Rating Technique (SMART) method to enhance effectiveness, objectivity, and transparency in scholarship selection. The system is built using the Laravel 11 framework and MySQL database, integrating selection criteria such as academic achievement, financial condition, and aspects of Al-Qur’an memorization for the Tahfidz scholarship. System testing is performed using the black-box method, accompanied by verification by comparing the results with manual selection. The research results show that this system can perform calculations and ranking of scholarship candidates more quickly and accurately, while successfully reducing subjectivity in decision-making.